The 'othering' in pandemics: Prejudice and orientalism in COVID-19 - Debanjan Banerjee; Roy Abraham Kallivayalil; T S Sathyanarayana Rao (Indian Journal of Social Psychiatry, 2020)
Pandemics are not just medical phenomena. They affect the society at large, having long-lasting psycho-social implications. Throughout history, they have led to stigmatization, prejudice, “othering,” and blame. This amplifies hate and socioeconomic divisions, and the effect outlasts the outbreak itself by years to come. Traditionally, humankind has always fared better to deal with the pathogen causing the outbreak, rather than the resultant stigma and prejudice. In the pursue of biological cures for the infection, this vital social implication is unfortunately neglected. The coronavirus disease 2019 (COVID-19) has emerged as a global public health threat. As international borders are sealed, economies slashed, and billions quarantined at their homes in an attempt to contain the spread of infection, history repeats itself in the prevalent marginalization, blame, and stigma that are more contagious than the virus itself. This commentary traces back through the past to look at examples of orientalism and colonialism in pandemics and the resultant stigma, and also to highlight global perspectives of the prevalent prejudice in this current outbreak of COVID-19.